Sigmund Freud, Hanns Sachs, and the apostle to the gentiles - Langton, Daniel R. (The journal of religion & society, 2008)
The study of Jewish approaches to Paul has tended to focus on theological issues. For some Jewish thinkers, however, the apostle was of interest for reasons other than interfaith dialogue or religious polemic. The psychoanalysts Sigmund Freud and Hanns Sachs discovered in Paul’s writings support for their own ideological concerns to offer a powerful critique of the place of religion in society. In terms of understanding Jewish-non-Jewish relations in the modern world, the study of how the Apostle to the Gentiles features in the works of these so-called marginal Jewish thinkers is a useful reminder of the complexity of Jewish identity.